2015
DOI: 10.3945/ajcn.114.103143
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental and noncompartmental modeling of 13C-lycopene absorption, isomerization, and distribution kinetics in healthy adults

Abstract: (13)C-Lycopene combined with physiologic compartmental modeling provides a strategy for following complex in vivo metabolic processes in humans and reveals that postabsorptive trans-to-cis-lycopene isomerization, and not the differential bioavailability of isomers, drives tissue and plasma enrichment of cis-lycopene. This trial was registered at clinicaltrials.gov as NCT01692340.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
1
51
1
Order By: Relevance
“…However, it has also been emphasized that ADME‐related factors, including digestion and matrix release, solubilisation in mixed micelles, epithelial uptake in the (small) intestine, and further bio‐distribution, all prerequisites for exerting potential biological effects, can be different between individuals. This likely results in variable blood/tissue concentrations . However, blood plasma/serum alone may not constitute the best indicator to assess carotenoid status, and additional methods, such as isotopic labelling, similar as for retinoids or easy accessible compartments such as white blood cells or buccal cells , may allow for more insights regarding endogenous carotenoid levels, carotenoid compartments, and turnover .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been emphasized that ADME‐related factors, including digestion and matrix release, solubilisation in mixed micelles, epithelial uptake in the (small) intestine, and further bio‐distribution, all prerequisites for exerting potential biological effects, can be different between individuals. This likely results in variable blood/tissue concentrations . However, blood plasma/serum alone may not constitute the best indicator to assess carotenoid status, and additional methods, such as isotopic labelling, similar as for retinoids or easy accessible compartments such as white blood cells or buccal cells , may allow for more insights regarding endogenous carotenoid levels, carotenoid compartments, and turnover .…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope labeling provides an alternative low-risk approach, where 13 C-labeled carotenoids can be consumed at concentrations found in the diet. This strategy has been used to study β-carotene absorption and conversion to vitamin A [ 16 , 17 ], as well as lycopene [ 18 ] and phytoene [ 19 ] pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence to suggest that the cis -lycopene isomer has any additional health benefits over the trans - form. Kinetic studies in adults have shown that the proportion of cis -lycopene isomers increase over time, and trans -lycopene isomers have a shorter half-life than cis -lycopene isomers [ 25 , 26 ]; however, the kinetics of lycopene isomers have not been studied in neonates. Therefore, we could speculate that the beneficial effects of lycopene on growth are more profound after the conversion of trans-lycopene to the more biologically active cis -lycopene, and mechanisms by which this conversion is performed may be immature in a newborn infant.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in analytical technology in recent years have led to the discovery that lycopene in human blood and tissue is distributed among 10–20 different isomers [ 25 ]. Typical food sources of lycopene contain 60–95% trans -lycopene [ 25 ], however; tissue and plasma have higher concretions of cis -lycopene, possibly due to post-absorptive trans -to- cis -lycopene isomerization [ 26 ]. However, the transfer from mother to fetus of these isomers, or differing impacts on maternal-newborn outcomes, has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%